Dynamics of Figurative-Stylistic Evolution of Solo Arrangement of the Folk Song (From «Zharty, kokhannya, lyubov ta zhenykhannya» / «Jokes, Love and Marriage» to «A my nashu slavnu Ukrayinu rozveselymo!» / «We Will Cheer Up Our Glorious Ukraine!») - Kuzyk, V. (Народна творчість та етнологія, 2023)
The article highlights the dynamics of the movement of artistic thought of the Ukrainian community in 1900–1918 on its way to the first attempt to form its own independent state. The data provided on the settlement and number of Ukrainians in the specified period is intended to show a large-scale panorama of the development of the most common genres of music making in everyday life because the universally recognized feature of the Ukrainian mentality as cordocentric already conditioned the desire for artistic self-expression, music, and singing. The author’s attention is focused on the genre of arrangement of Ukrainian folk songs for voice with instrumental accompaniment, which created a powerful folklore wave associated with the trends of increased national self-determination and democratization of the aesthetic foundations of Ukrainian art. The policy of the russian tsarist culturists of that time was aimed at spreading the so-called «Little russian surrogate»—encouraged the publication of artistically inferior songs that had humorous, entertaining, love-sentimental, burlesque, or frankly vulgar content. However, the purposeful patriotic activity of such artists as M. Lysenko, K. Kvitka, K. Stetsenko, O. Koshyts, B. Yanovsky, Yа. Stepovy, F. Kolessa, O. Nyzhankivskyi, D. Sichynskyi, and S. Charnetskyi caused a significant evolution of the genre of solo arrangement, raising it to the high level of a vocal miniature / romance, defined by the purely Ukrainian musical term «solospiv» ≈ «solosиng». The evolutionary growth significantly affected the topic of the genre when songs of civic pathos, full of pride for the heroic past and the desire for national self-determination and statehood, began to gain national popularity.